Extracts of Vine Tea Improve Diet-Induced Non-Alcoholic Steatohepatitis Through AMPK-LXRα Signaling - Chen, Yu-jun; Song, Hai-yan; Zhang, Zi-wei; Chen, Qian; Tang, Zhi-peng; Gu, Ming (Frontiers in Pharmacology, 2021)
Chinese vine tea can improve glucose and lipid metabolic disorders. However, its protective eﬀects in non-alcoholic steatohepatitis (NASH) and its underlying molecular mechanisms remain unclear. Liver X receptor α (LXRα) inhibition and adenosine monophosphate-(AMP)-activated protein kinase (AMPK) activation can enhance control of NASH. AMPK activators have also been shown to inactivate LXRα. Here, the anti-NASH effects of vine tea extract (VTE) dosed at 1 g.100 g-1 diet were investigated using NASH mice challenged with a methionine and choline-deficient L-amino acid diet (MCDD) and a high-fat diet (HFD). Pharmacological mechanisms of VTE were explored using TUNEL staining, AMPK inhibition, Western blot, reporter assays, qRT-PCR analyses, and immunofluorescence. VTE treatment improved fatty liver in HFD-induced mice, while it alleviated the progression of NASH including protecting against liver lipid accumulation, steatosis, endoplasmic reticulum stress, apoptosis, inflammation, and functional injury in MCDD-fed mice. VTE reduced the action of hepatic lipogenic genes, F4/80, pro-inflammatory cytokines, CHOP, and cleaved Caspase-3 expression, while promoting expression of fatty acid oxidation genes CPT1α, β. VTE also enhanced AMPK and blocked LXRα signaling in mouse livers. In vitro results indicated that VTE increased AMPK phosphorylation and reduced LXRα activity in HepG2 cells. Conversely, the antagonistic effect of VTE on LXRα was decreased through AMPK inhibition. . Our data suggests that VTE may improve diet-induced NASH, which involves the pharmacological modulation of the AMPK- LXRα signaling pathway.